The effect of strength training for muscular balance in the development of leg muscles to prevent sprains ankle joint Taekwondo players ages (11-13 years) - Abdul Naby, Hamid; Caliph, Emad (Journal of Physical Education, 2015)
The prevention of injuries and one of the important basic science and specialized in the field of sports medicine which is used and apply the preventive and curative exercise, to prevent sports injuries or avoided, most of injuries were sprains injuries in the ankle joint, where they can prevent injuries significantly in individuals who have never injured ankle sprains, through the development of muscle supporting detail, and through the built-up curriculum development on a scientific basis in training, where the number of the sample (12) players of ages (11-13 years), was this sample is divided into equal groups, one of them an officer and the other trial, the researcher developed a set of exercises force in the development of muscular balance of the leg muscles to prevent sprains ankle joint using the tools and training tools, has lasted for preventive units (8) weeks of (3) units per week, preventive Module time (15-20 minutes), as the researcher concluded that the application of strength training used a positive impact in strengthening joint muscles of the ankle with the experimental research sample individuals, was evident through pre and post tests and who appeared by evolution with the sample, the researcher recommends the use of strength training for the prevention of the occurrence of injuries, when you use a preventive strength training should be jointly between the trainer and physical therapist in order to determine the type of weakness in the muscles that need strengthening and the type and intensity of exercise required and the frequency and duration of her palm